Pengaruh Komitmen Organisasional dan Motivasi Kerja terhadap Kinerja Pegawai Badan Kepegawaian Daerah Provinsi Maluku Utara Melalui Disiplin Kerja - Suwardi Habib; Abdul Rahman Jannang; Marwan Man Soleman (Peneliti.net, 2022)
This study aims to examine organizational commitment and work motivation on employee performance by considering work discipline as a mediator. A total of 129 responses were collected through the distribution of questionnaires to employees of the Regional Personnel Agency (BKD) of North Maluku Province using the saturated sample technique. The analytical technique used in this study is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS version 3.3 application. The results of the analysis show that organizational commitment has a positive and significant effect on work discipline. Work motivation has a positive and significant effect on work discipline. Organizational commitment has a positive and significant effect on employee performance. Work motivation has no significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Work discipline positively mediates the effect of organizational commitment on employee performance. Work discipline positively mediates the effect of work motivation on employee performance